Effects of bacterial inoculant biofertilizers on growth, yield and nutrition of rice Australia. (23rd February 2016) - Kecskés, M. L.; Choudhury, A. T. M. A.; Casteriano, A. V.; Deaker, R.; Roughley, R. J.; Lewin, L.; Ford, R.; Kennedy, I. R.
ABSTRACT: Inoculant biofertilizer application increased fertilizer nitrogen (N) use efficiency in Vietnam in some previous field experiments. Similar results may be obtained in Australia. With this view in mind, a greenhouse experiment and two field experiments were conducted using a Vietnamese inoculant biofertilizer (BioGro) and several other plant growth promoting (PGP) bacteria. In the greenhouse trial, bacterial inoculations increased shoot and root weights of rice plants significantly. In the field experiments, particularly with Rhizobium leguminosarum, similar effects including significant differences in nitrogen uptake in vegetative matter were observed at the panicle initiation (PI) stage. However, these effects were not significant on grain yield at harvest and it is concluded that the much longer period of growth for Australian rice may allow compensation between treatments. Re-inoculation of plants at the PI stage, and lower application rates of N fertilizer in at least two splits are suggested for future field experiments.